Dose caffeinated energy drink is a consideration issue for endurance performance - Wang, Jie-Ping; Wei, Chen-Chan; Peng, Yun-Dong; Wang, Hsuan-Yun; Hung, Chi-Hsiang; Hong, Yin-Hui; Liou, Yuh-Feng; Hou, Chien-Wen (Frontiers in Physiology, 2022)
Caffeinated energy drinks are commonly taken to improve exercise performance, but there are few studies on the influence of different doses on an athlete’s performance. We conducted a double-blind, randomized, counter-balanced, and crossover research study to examine the effects of low caffeinated energy drink (Low ED) or high caffeinated energy drink (High ED) supplement on the performance, haematological response, and oxidative stress in triathletes. Twelve male participants underwent three testing sessions separated by weekly intervals, consisting of sprint triathlon training (0.75 km swim, 20 km cycle, and 5 km run). Before and during the trials, participants were randomly provided with either placebo (PLA) group, Low ED group, or High ED group. Exercise performance in the High ED group decreased significantly compared with the PLA and Low ED groups (p < 0.05). However, participants in the Low ED group also experienced an improved performance (p = 0.054). Analysis of variance revealed no differences among the three groups in cortisol and testosterone levels, or the Borg Rating of Perceived Exertion score (p > 0.5). Furthermore, superoxide dismutase (SOD) was reduced with exercise and were lowest in the High ED group. However, compared with PLA, a significant decrease of thiobarbituric acid reactive substances (TBARS) was observed in Low ED and High ED groups (p < 0.05). This indicates that caffeinated energy drink consumption may improve performance and reduce oxidative stress in sprint triathlon athletes. However, individual differences should be considered when supplementing with caffeinated energy drinks to decrease side effects.